(untitled) (Bangladesh Journal of Botany, 2020)
Ultrasonication assisted extraction (UAE) was employed to extract total flavonoids (TF) from Kaempferia galanga L. (KGL) roots. Single-factor experiments were performed to evaluate the effects of the process parameters (solvent-to-material ratio, ethanol concentration, extraction time, ultrasonic power, and extraction temperature) on the TF yield and the response surface methodology (RSM) was used to optimize the extraction parameters. The optimum conditions to obtain the maximum TF yield were solvent-to-material ratio, 25; ethanol concentration, 62%; extraction time, 27.0 min; extraction temperature, 50℃ and ultrasonic power, 225 W. The yield of TF under these conditions reached 3.22 ± 0.12 mg/g of dry root. The analysis of variance and validation test indicated that the proposed method is useful and reliable. The antioxidant capacities of TF of KGL was determined by DPPH· and ABTS+· methods, which revealed that it has good antioxidant activity in both systems.